SIFAT FISIKA PAPAN SEMEN PARTIKEL PELEPAH RUMBIA - Gusti Ahmad Rahmat Thamrin (Jurnal Hutan Tropis, 2011)
ABSTRACT. Manufacture of cement particle board and testing physical properties are implemented in the laboratory of panels of wood forest products Technology majors Lambung Mangkurat University. Research on physical properties include water content, density, water absorption, and the development of thick. The experimental use is a random complete ral ( 2 ) nonfaktorial by remedial treatment and 5 times , a particle that is making cement with raw materials pelepah rumbia without the skin and cement making a particle with raw materials pelepah rumbia with skin . Standard used for comparison is SNI-03-2104-1991 .The average levels of the water between the semen of a particle midrib metroxylon sagu without the skin and board cement particles midrib metroxylon sagu with skin successive adalah13,02 % and 10,75 %. Both treatment entry in the SNI (maximum 14%). The average value of the density of the particle cement board without bark and branches and kiray cement particle board with the skin in a row as kiray is 0.73 gr/cm3 and 0.90 gr/cm3. Both treatment entry in the SNI (minimum 0.57 per gr/cm3).The average value of water absorption of cement particle board as kiray without skin and cement particle board with the skin in a row as kiray is 43,86% and 35.86%. The second treatment was not entered in the SNI (10-30%).Keywords: cement particle board, Rumbia’s MidribABSTRAK.    Pembuatan papan semen partikel dan pengujian sifat fisika dilaksanakan di Laboratorium Panel-Panel Kayu jurusan Teknologi Hasil Hutan Universitas Lambung Mangkurat. Penelitian sifat fisika meliputi kadar air, kerapatan, penyerapan air, dan pengembangan tebal. Rancangan percobaan yang digunakan adalah Rancangan Acak Lengkap (RAL) nonfaktorial dengan 2 perlakuan dan 5 kali ulangan, yaitu pembuatan papan semen partikel dengan bahan baku pelepah rumbia tanpa kulit dan pembuatan papan semen partikel dengan bahan baku pelepah rumbia dengan kulit. Standar yang digunakan untuk perbandingan yaitu SNI-03-2104-1991. Nilai rata-rata kadar air antara papan semen partikel pelepah rumbia tanpa kulit dan papan semen partikel pelepah rumbia dengan kulit berturut-turut adalah13,02% dan 10,75%. Kedua perlakuan masuk dalam SNI (maksimum 14%). Nilai rata-rata kerapatan antara papan semen partikel pelepah rumbia tanpa kulit dan papan semen partikel pelepah rumbia dengan kulit berturut-turut adalah 0,73 gr/cm3 dan 0,89 gr/cm3. Kedua perlakuan masuk dalam SNI (minimum 0,57 gr/cm3).Nilai rata-rata penyerapan air antara papan semen partikel pelepah rumbia tanpa kulit dan papan semen partikel pelepah rumbia dengan kulit berturut-turut adalah 43,86% dan 35,86%. Kedua perlakuan tidak masuk dalam SNI (10-30%). Nilai rata-rata pengembangan tebal antara papan semen partikel pelepah rumbia tanpa kulit dan papan semen partikel pelepah rumbia dengan kulit berturut-turut adalah 2,57% dan 1,79%. Kedua perlakuan masuk dalam SNI (maksimum12%). Perlakuan tidak berpengaruh nyata terhadap kadar air dan pengembangan tebal.Kata Kunci:   Papan semen partikel, pelepah rumbia